Shock in children - Carlotti, Ana Paula Carvalho Panzeri (Medicina (Ribeirao Preto), 2012)
This paper presents a review of the definition, classification, pathophysiology and initial management ofthe different types of shock in children. Early recognition and aggressive treatment of shock in a timelymanner are essential to the prevention of cardiopulmonary arrest and outcome improvement.